1989
DOI: 10.1037/0021-9010.74.5.787
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of concrete cognition to emotion: Neutral symptoms as elicitors of worry about cancer.

Abstract: The relationship between worry about cancer and judged cancer risk was examined among 54 expatients who had been cured of breast cancer and 81 women with no history of cancer. Worry required both a perception of substantial risk and the presence of concrete perceptual cues. Worry promoters include visits to a physician and concrete, noncancerlike symptoms (e.g., fever, pain). Supporting analyses indicate that the symptom effects are not due to self-report biases or attributions of symptoms to cancer but are th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
118
2
7

Year Published

1997
1997
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(132 citation statements)
references
References 31 publications
5
118
2
7
Order By: Relevance
“…Many cancer researchers have commented on how the fear of recurrence may be triggered and maintained by persistent physical distress: especially by distress similar to that caused by the active cancer. 30,31 Similar observations have been made in breast cancer survivors, who indicated that their fear of recurrence was triggered by physical signs on their breasts, such as a change in color or swelling, that reminded them of the initial cancer. 32 Our patients with NPC who had gone through RT faced the same kind of problem, which that made complacency unlikely.…”
Section: Adjustment At 2 To 4 Monthsmentioning
confidence: 59%
“…Many cancer researchers have commented on how the fear of recurrence may be triggered and maintained by persistent physical distress: especially by distress similar to that caused by the active cancer. 30,31 Similar observations have been made in breast cancer survivors, who indicated that their fear of recurrence was triggered by physical signs on their breasts, such as a change in color or swelling, that reminded them of the initial cancer. 32 Our patients with NPC who had gone through RT faced the same kind of problem, which that made complacency unlikely.…”
Section: Adjustment At 2 To 4 Monthsmentioning
confidence: 59%
“…Esto es coherente con las hipótesis actuales sobre la hipocondría que apuntan hacia la hipervigilancia de las propias sensaciones corporales como un factor importante en el desanrollo y mantenimiento de la enfermedad (Easterning y Leventhal, 1989;Warwick y Saikovskis, 1990;Hitchcock y Mathews, 1992;Avia, 1993). Además, la continua manipulación de sus senos le llegó a producir una importante irritación y la aparición de hematomas en esta zona, lo cual servía por sí mismo como estímulo desencadenante de las cogniciones hipocondríacas y la posterior conducta de exploración.…”
Section: 23-hipótesis Explicativaunclassified
“…Among the concepts, fear is considered in two different forms: fear of gaining weight, proposed as a motivator (Witte, 1998) of intention and fear of sweeteners, the ingredients used to sweeten sugar-free drinks, proposed as an inhibitor (Witte, 1998). Fear has been conceptualized as "a negatively-valenced emotion, accompanied by a high level of arousal (Witte, 1998) and elicited by a threat that is perceived to be significant and personally relevant" (Easterling & Leventhal 1989;Lang 1984;Ortony & Turner 1990, Witte 1992). In the case that fear of gaining weight is related to the negative reinforcement, often used in fear advertising appeals.…”
Section: Emotional Factorsmentioning
confidence: 99%